Phenotypic variation of Leptodactylus cupreus Caramaschi, São-Pedro and Feio, 2008 (Anura, Leptodactylidae) - Cassini, Carla S.; Orrico, Victor G. D.; Dias, Iuri Ribeiro; Solé, Mirco; Haddad, Célio F. B. (Zootaxa, 2013)
This study describes for the first time the female of Leptodactylus cupreus and provides new information concerning its geographical distribution, male’s morphology and bioacustics. Leptodactylus cupreus, a poorly known species from the Brazilian Atlantic Forest, was originally allocated in the L. mystaceus complex of the L. fuscus species group. Based on morphological observations, we infer that L. cupreus should be in fact related to L. mystacinus, a species that, although assigned to the L. fuscus species group, is not assigned to the L. mystaceus complex. Therefore, we comment the phylo-genetic relationships concerning L. cupreus, L. mystaceus and L. mystacinus.